Retrospective analysis of the role of Ulinastatin in reducing mortality in severe pancreatitis in critical care unit in Nepal - Khadka, Bikash; Adhikari, Hemant; Poudel, Saroj; Khanal, Kishor (Journal of Advances in Internal Medicine, 2021)
Background: Acute pancreatitis sequelae require a multidisciplinary approach and ICU care. Ulinastatin is a serine proteases inhibitor that reduces inflammation by suppressing the infiltration of neutrophils and elastase release and inflammatory mediators that help improve clinical symptoms and reduce mortality. This study aims to evaluate the clinical utility of Ulinastatin. Methods: Fifty-two patients admitted to ICU with acute pancreatitis were divided into; Ulinastatin group who received a 3 to 5 days course of 200,000IU, and Control Group who didn’t receive ulinastatin. Pearson’s Chi-square and Fisher’s exact test were used and a p-value < 0.05 was considered statistically significant. Results: Mean age was lower among the Ulinastatin group at 43 years (p-Value 0.014) and Hepatic dysfunction was more among this group (p-value 0.04). Among new onset of organ dysfunction, only CVS dysfunction was significant among the Control group ( p-value 0.044) while respiratory function recovery (p-value 0.04) and coagulation profile improvement (p-value 0.017) was statistically significant among the Ulinastatin group. The mean duration of hospital stay was shorter among control group, 9.65 days vs 14 days, a p-value of 0.05and also the average duration of stay in MDICU was lower, 4 days vs 8.5 days, p-value 0.0044 in comparison to Ulinastatin group. Overall mortality incidence was 15.38%, 19% in Ulinastatin group vs 11.5% in Control group. Conclusion: This retrospective study is our experience in the use of Ulinastatin which has shown little efficacy in declining mortality and/or hospital stay duration though it helps prevent new organ dysfunctions.